A inadimplência agropecuária no Mercosul: o caso dos arrozeiros - Machiavelli Filho, Alvaro Luiz (2005)
This research is a study on insolvency in agricultural activity in Mercosul countries, from 1990 to 2003. In 1990, rice farmers insolvency started in Brasil, in Argentina and Uruguai it started five years later. The how and the why the crises arouse in these countries in the rice sector as well as the government and banks decisions in order to solve it are dicussed in the fisrt part of the paper. In the second part, the particular situation of Rio Grande do Sul, the main rice producer of Brasil, is discussed. A group of 1% of the rice farmer of the State was separated into three groups. The first group included the farmers who passed through the crisis with few problems and had no rstrictions to get oficial credits. The second group included farmers that had problems during the crisis but now they acceed to oficial creditsagain. The farmers of the third group also suffered the crisis, they could not overcome it and nowadays they don´t get bank credits. Bibliography review was the methodology for developing the first part or the research. For the second part, in order to get farmers information a questionaire was constructed. The conclusions show that agricultural crisis started in Brasil before than in Argentina and Uruguai as well as the solutions in those countries followed the ones in Brasil. All of them had strong government intevention. In relation to the farmer groups, it was detected that age, schooling and productivity among other parameters influenced their behaviors.